2015
DOI: 10.1159/000439581
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Access and Delivery of Continuous Renal Replacement Therapy Dose

Abstract: Aims: The study aims to describe the use of dialysis catheters in critically ill patients treated with continuous renal replacement therapy (CRRT) and to study the impact of femoral versus non-femoral access on CRRT dose. Methods: Statistical analysis and predictive modelling of data from the Randomized Evaluation of Normal vs. Augmented Level renal replacement therapy trial. Results: The femoral vein was the first access site in 937 (67%) of 1,399 patients. These patients had higher Acute Physiology and Chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 16 publications
0
14
0
1
Order By: Relevance
“…4 Continuous Renal Replacement Therapies (CRRT) relies on the maintenance of extracorporeal circuit (EC) patency for as long as possible, however premature circuit failure due to clotting may cause blood loss, reduced therapeutic efficacy and increased workload and treatment costs. [5][6][7][8] Clogging and clotting of the hemofilter membrane is the major mechanism of premature failure and circuit loss in CRRT. 9,10 It has been suggested that increasing blood flow rate (BFR) through the EC to speeds greater than 200 mL/min may reduce premature clotting.…”
Section: Introductionmentioning
confidence: 99%
“…4 Continuous Renal Replacement Therapies (CRRT) relies on the maintenance of extracorporeal circuit (EC) patency for as long as possible, however premature circuit failure due to clotting may cause blood loss, reduced therapeutic efficacy and increased workload and treatment costs. [5][6][7][8] Clogging and clotting of the hemofilter membrane is the major mechanism of premature failure and circuit loss in CRRT. 9,10 It has been suggested that increasing blood flow rate (BFR) through the EC to speeds greater than 200 mL/min may reduce premature clotting.…”
Section: Introductionmentioning
confidence: 99%
“…The choice of dialysis catheter location will likely continue to depend on physician experience and patient characteristics, for example, patients with high BMI receiving internal jugular catheters. Femoral catheters often are, and likely will remain, the site of choice in the cases of emergencies (1, 16). …”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this study is the first to assess the risk of DC dysfunction when DCs are placed by GWE rather than by VPI in the ICU setting. Several characteristics may predispose to DC dysfunction such as catheter material [ 26 ], length [ 10 ], gauge [ 27 ], insertion site [ 10 ] and blood flow velocity through the DC [ 10 ]. In the ELVIS study the DC characteristics and causes of DC dysfunctions were not recorded, which restricted our ability to elaborate on the mechanisms involved.…”
Section: Discussionmentioning
confidence: 99%